Liminares nas ações de despejo - Teperman, Marcel (2015)
Preliminary injunctions on the course of civil lawsuits are a way of guaranteeing the effectiveness of the law on urgent matters. The accurate comprehension of the various kinds of preliminary injunctions found on the “Renter’s Law” and the correct implementation of them, allow the operators of law to guarantee and apply the correct right according to the concrete case. This work also studies the appeals against the preliminary injunctions, as well as cases that are not expressly found on the law, but are also righteous to receive the injunction.